The Role of Digital Applications in the Promotion of Citizens' Health to Accelerate the Leadership of Rural Public Health Services - Gunawan Widjaja (Science Midwifery, 2022)
This study discussed the role of digital technology applications in promoting public health efforts to accelerate technology-based health services. Our efforts to obtain data have been carried out in many journals and information sources related to health services and technology. We find the data electronically by searching for keywords. Then we analyze it under a phenomenological approach, which tries to understand health issues based on digital application technology. In our studies, we chose methods of the data coding system, in-depth analysis, high evaluation of the data, and interpreting the data to obtain valid and convincing findings. So, based on the findings that we have presented as well as the results of the discussions that we have conducted, we can say that the role of digital applications in efforts to accelerate health services and promotions for the community in the regions has given a belief that this digital application is indeed efficient and profitable because it can innovate services and also the acceleration of services from the government to people who need technology-based health services in the all-digital era. Hopefully, these findings will support further studies, especially among academics and practitioners in the field.